The impact of racial identity and school composition on affirmative action attitudes of African American college students. (2nd November 2022) - Awad, Germine H.; Tran, Kimberly; Hall-Clark, Brittany; Chapman-Hilliard, Collette; Dillard, Jendayi; Payne, Taylor; Hess, Elaine; Jackson, Karen
ABSTRACT: Affirmative Action remains a controversial policy that incites a variety of reactions. Some believe it's an unjust policy that discriminates against applicants, while others view it as a policy aimed at fighting against past inequalities and discrimination. Little is known about African American endorsement of the policy. Two hundred and seven Black students from a predominantly White institution (PWI) and a historically Black university (HBCU) participated in the current study to examine the impact of racial identity on affirmative action attitudes (AA). Results indicated that school type and race centrality significantly predicted AA attitudes. Students who attended a HBCU were less likely to endorse AA compared to students at the PWI and those higher in race centrality were more likely to endorse AA. This study is one of the first to investigate the impact of the educational environment on the affirmative action attitudes of African Americans.